Proposed Hybrid Algorithm for Generate Database Index Key Based on Image Contents - Abdulwahab, S. T.; Jabbar, E. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper deals with proposing new lifting scheme (HYBRID Algorithm) that is capable of preventing images and documents which are fraud through decomposing there in to the real colors value arrays (red, blue and green) to create retrieval keys for its properties and store it in the database and then check the document originality by retrieve the query image or document through the decomposition described above and compare the predicted color values (retrieval keys)  of the query document with those stored in the database. The proposed algorithm has been developed from the two known lifting schemes (Haar and D4) by merging them to find out HYBRID lifting scheme. The validity and accuracy of the proposed algorithm have been evaluated through experiments with the decomposition of database image consists of important documents like college certifications up to maximal decomposition level of 14. The tests results using the HYBRID algorithm were compared with that of the other methods (Haar and D4 Lifting scheme) in terms of the accuracy of discovering forgeries (retrieval accuracy) and the required store memory area. The results illustrate that the HYBRID algorithm show better performance than the others in terms of the sensitivity to any change in the retrieval documents. Also, HYBRID Algorithm exhibits good improvement in terms of the used memory space compared to the results obtained by D4 Lifting scheme.